(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Fossil energy resources in Latvia are imported from other countries, but at the same time, our country is rich in renewable energy resources and other raw materials, which are used very little. In the study it is proposed to create a thermal insulation material from hemp shives grown in Latvia as a filler material and lake sediment - sapropel as a binding agent. Both of the following materials are organic, renewable and locally available. Laboratory experiments show that ecological and complying with modern requirements thermal insulation material can be obtained from local, renewable raw materials: sapropel and hemp shives.